EMPOWERMENT OF COFFEE FARMERS IN IMPROVING COMMUNITY WELFARE IN BOKON VILLAGE - Kobak, Raena; Frank, Simon Abdi K; Poli, Agustina Ivonne; Idris, usman (International Journal of Social Science, 2024)
This study aims to analyze the empowerment of coffee farmers in Bokon Village, Tiom District, Lanny Jaya Regency, Papua, as an effort to improve community welfare. The urgency of this research lies in the challenges faced by farmers, such as low productivity, limited access to technology and information, and low quality of human resources. This research uses a qualitative approach with a field study method, involving in-depth interviews, participatory observation, and document study to collect primary and secondary data. The results show that empowerment through coffee farmer groups has had a positive impact on the income and welfare of local communities. Innovations in cultivation techniques, such as the utilization of shade plants and organic fertilizers, have successfully improved the quality of coffee production. However, the main challenges are still related to the low education level of farmers, the lack of interest of the younger generation to engage in the agricultural sector, and the lack of infrastructure support and market access from the government. The empowerment of coffee farmers in Bokon Village has great potential in improving the socio-economic conditions of the community. Increased government attention is urgently needed in the form of training, technical assistance, and expansion of marketing networks to support the sustainability of coffee farmer empowerment and the regeneration of young farmers in the region